The People Link : Human Resource Linkages across The Pacific - Safarian, A. E. (Book collections on Project MUSE., 1997)
The purpose of this volume is to illuminate the links among the peoples of the region that Canadians needs to understand when doing business abroad or cooperating with East Asians in North America.